(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The development of professional competence among future physical education teachers is a critical aspect of higher education. This study explores effective strategies for enhancing the professional capabilities of physical education students, emphasizing pedagogical skills, subject knowledge, and practical experience. The research examines modern methodologies, including digital learning tools and interdisciplinary approaches, to ensure comprehensive teacher training. The findings suggest that integrating innovative techniques significantly improves teaching efficacy and student engagement.